Evaluation of Pedestrian Facilities in the Kuta Tourism Area (Case Study: Kuta Beach Road) - Tapa, I Gede Fery Surya; Kumara, I Nyoman Indra; Indrashwara, Decky Cipta; Putri, Putu Indah Dianti; Wedagama, Dewa Ayu Trisna Adhiswari (Universitas Ibn Khaldun Bogor, 2025)
The Kuta Tourist Area is a tourist area dominated by tourists who prefer to walk rather than use motorized vehicles to carry out their activities. The aim of this research is to determine the characteristics of pedestrians, determine the types of pedestrian facilities, and provide recommendations for appropriate pedestrian facility designs in the Kuta Tourism Area, especially on Kuta Beach Road. The method used in this research refers to the regulations of Minister of Public Works No.34 of the year 2014. The calculation results show that on weekdays the largest pedestrian flow occurs in the afternoon on the East sidewalk with a total of 364 people/m/hour, the average speed of space is 3.33 km/hour, density is 11 people/100m2, space is 9 .17 m2/person, and the level of service for pedestrian facilities is in category B, while on the South sidewalk the largest pedestrian flow is 202 people/m/hour, the average speed of space is 3.33 km/hour, the density is 6 people/100m2 , space is 16.49 m2/person, and the level of service for pedestrian facilities is in category A. Furthermore, on weekends the largest pedestrian flow occurs in the afternoon on the East sidewalk with a total of 765 people/m/hour, the average speed space 3.13 km/hour, density 24 people/100m2, space 4.09 m2/person, and the level of service for pedestrian facilities is in category B, while on the West sidewalk the largest pedestrian flow is 131 people/m/hour, speed the average space is 3.41 km/hour, the density is 4 people/100m2, the space is 26.09 m2/person, and the level of service for pedestrian facilities is in category A.